Implications Méthodologiques des fouilles de Tuvaaluk sur l'étude des établissements dorsétiens [The Methodological Implications of the Tuvaaluk Programme Excavations on the Study of Dorset Sites] - Plumet, Patrick; Badgley, Ian (ARCTIC, 1980)
In the hope of obtaining paleoethnographic data, Tuvaaluk Programme excavations have focused on zones implying Dorset domestic and social organization. The principal site initially selected appeared to comprise diverse habitations with semi-subterranean dwellings, three of which are partially overlapping. The horizontal extension of the excavation into interstructural zones, the registration of structural remains by vertical photography, and analysis of the natural stratigraphy revealed a much more intensive occupation of the excavated area than was originally anticipated. . Thus, the systematic and intensive excavation of a site initially perceived as relatively simple reveals a variety and complexity of features that would not have been found by the sampling and limited excavation of visible habitations and a supposed midden. Resulting interpretations and hypotheses concerning, in particular, use of the site, seasonality, demography, and the regional settlement pattern, are consequently significantly altered. Les fouilles de Tuvaaluk ont été orientées vers l'étude de l'espace domestique et social dorsétien dans l'espoir d'en obtenir des données palethnographiques. Le site principal, choisi au départ, semblait correspondre á des habitats divers avec maisons semi-souterraines dont trois étaient partiellement enchevêtrées. L'extension horizontale de la fouille dans l'espace interstructural, l'enregistrement des structures-témoins par photographie verticale, l'analyse de la stratigraphie naturelle ont révélé une occupation intensive de l'espace fouillé très différente des prévisions. Elle correspond à une série de réaménagements fortement inbriqués les uns dans les autres, à différentes saisons et différentes époques de la période dorsétienne. Ainsi, la fouille systématique et intensive d'un site apparaissant relativement simple au départ révèle des facies variés et complexes que des sondages et des fouilles restreintes aux structures visibles et au dépotoir supposé n'auraient pas décelés. Les interprétations et ...